1990
DOI: 10.3758/bf03337658
|View full text |Cite
|
Sign up to set email alerts
|

A test of resource-allocation explanations of the generation effect

Abstract: Several current theories of the generation effect posit that generated items receive greater encoding resources than do read items in the same list. These theories were tested, by asking subjects to pay special attention to target items embedded in a list of background items. Targets were either read or generated, and received either normal or special attention. Background items were always read. Compared to memory for words in a list of read target and background items, memory for generated targets was enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Thus, across all comparisons, increased recall of generated targets was accompanied by a similar decrease in recall of intact background items. This trade-off replicates results reported by Slamecka and Katsaiti (1987) and Schmidt (1990). One interpretation of the trade-off is that generated-items "rob" encoding resources from intact items in the same list (Schmidt, 1990).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, across all comparisons, increased recall of generated targets was accompanied by a similar decrease in recall of intact background items. This trade-off replicates results reported by Slamecka and Katsaiti (1987) and Schmidt (1990). One interpretation of the trade-off is that generated-items "rob" encoding resources from intact items in the same list (Schmidt, 1990).…”
Section: Discussionsupporting
confidence: 88%
“…This trade-off replicates results reported by Slamecka and Katsaiti (1987) and Schmidt (1990). One interpretation of the trade-off is that generated-items "rob" encoding resources from intact items in the same list (Schmidt, 1990). Thus, generation leads to increased individual-item processing as a result of increased attention given to generated items.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kinoshita (1989, Experiment 4) found that subjects who correctly copied a word originally presented with two underlined, transposed letters performed better on later recognition of the items than did subjects who simply copied correctly spelled words (though this effect did not obtain with free recall as the final test). In addition, Schmidt (1990) found that words for which subjects copied a missing letter (printed to the right of the word) onto the correct blank space embedded in the word were later more likely to be recalled than words that were simply studied in whole form. Another, more likely, possibility is that the generation effect is often due to the combined beneficial effects of retrieval plus the extra processing of the target material demanded by the generation task.…”
Section: Relation To the Generation Effectmentioning
confidence: 99%
“…What is critical in producing a generation effect is that the retrieval procedure tap the chosen generation strategy (Nairne, 1988;Nairne & Widner, 1987). Schmidt (1990) has concluded that generation promotes individual item processing at the expense of a more global (e.g., whole-list) processing; thus the effect is most likely when subjects have both the opportunity to read and to generate items in the same list (i.e., the mixed-list format). We believe, and we have assumed, that generation in advertising contexts closely resembles a mixed-list experiment format: Some ads use generation techniques, and some do not.…”
Section: Generation Effects With Advertising Stimulimentioning
confidence: 99%